ANTARA AGAMA DAN BISNIS BISNIS DALAM PANDANGAN ISLAM - M. Zikwan (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
Business is an effort made by someone or more to make ends meet through production activities, or buying and selling of products. Some circles say that business is an activity to make as much profit as possible, so religion cannot be combined with business. Islam is not an anti-business religion but Islam is a religion that regulates business activities. The spirit of Islamic business is Islam, Iman and Ihsan. The principles of business in Islam are the principles of Illahiyah, the principles of Nubuwwah, the principles of al-Adaliyyah, the principles of al-Hurriyah, the principles of al-Musawwah, the principles of Ta'awun. Islam is not a religion that prohibits business, but Islam is a religion that supports business activities. Prophet Muhammad as the bearer of the message of Islam, including business people, more than that the Prophet Muhammad was the pioneer of business in Islam. Islam has never prohibited the ummah from doing business, even Islam gives the value of freedom in doing business activities.